Effect of 3% diquafosol sodium eye drops on the prediction of intraocular lens power in predisposition to dry eye patients scheduled for cataract surgery: a prospective, observational study - Su, Na; Ge, Lexin; Tang, Nianfeng; Shan, Junjie; Fan, Wen; Yuan, Songtao (Frontiers in Medicine, 2025)
PurposeTo investigate the effect of 3% diquafosol sodium eye drops (DQS) on intraocular lens (IOL) power calculated by multiple common formulas before surgery in patients with predisposition to dry eye (p-DE) scheduled for cataract surgery.MethodsThis prospective, observational study included patients scheduled for cataract surgery at the Ophthalmology Clinic of Jiangsu Provincial People’s Hospital between July 2022 and July 2023. A total of 50 eyes underwent repeated measurements to assess instrument stability, while 91 were divided into p-DE and control groups with mean tear break-up time (mBUT) <10 s and mBUT ≥10 s, respectively. Biological indexes were measured 5 min after DQS use in both p-DE and control groups.ResultsFollowing DQS eye drops application, the p-DE group exhibited a higher number of eyes with changes in IOL power (calculated by SRK formula) and tear film stability (TFS) compared with the control group (p < 0.05) and the IOL power calculated by Hoffer Q formula also showed a statistical difference before and after DQS use (p < 0.05). After using DQS, the tear meniscus height (TMH), the first breakup time and the mBUT all increased in the p-DE group (p < 0.05), yet they were still lower than those in the control group. However, no significant differences were found in axial length, K value, corneal astigmatism axis, difference vector, anterior chamber depth, central corneal thickness, lens thickness, and white-to-white among all groups before and after DQS use (p > 0.05). Combined correlation analysis and logistic regression analysis revealed that changes in steep keratometry and TMH after treatment with DQS eye drops were the main factors affecting IOL power change. Additionally, mBUT before DQS use was identified as the primary factor affecting TFS change.ConclusionUse of 3% DQS induces changes in intraocular lens power by affecting steep keratometry values, with such change being more significant in predisposition to dry eyes and warranting attention. When planning cataract surgery, it is recommended to prioritize the Barrett Universal II formula for IOL power calculation.